P236Evaluation of safety and feasibility of Mybpc3 gene therapy in a mouse model of hypertrophic cardiomyopathy. (15th July 2014) - Mearini, G; Simpel, D; Geertz, B; Kraemer, L; Schlossarek, S; Weinberger, F; Mueller, O; Voit, T; Eschenhagen, T; Carrier, L
Abstract: Purpose: Hypertrophic cardiomyopathy (HCM) is characterized by left ventricular hypertrophy (LVH) and diastolic dysfunction, and is frequently caused by MYBPC3 mutations, which mainly result in haploinsufficiency of cardiac myosin-binding protein C (cMyBP-C). We recently provided proof-of-concept studies that adeno-associated virus (AAV)-mediated RNA-based therapies (exon skipping and trans-splicing) remove the mutation in a homozygous Mybpc3-targeted knock-in (KI) mouse model of HCM. However, the level of cMyBP-C remained low. In the present study, we evaluated the feasibility and safety of Mybpc3 gene therapy to correct cMyBP-C protein haploinsufficiency and prevent the cardiac phenotype in KI mice. Methods: FLAG-tagged Mybpc3 cDNA under the control of the human TNNT2 promoter was packaged in AAV9. Different doses of AAV9 (10^11, 3x10^11, 10^12, 3x10^12 viral genome (Vg)/mouse) or PBS were administered in the temporal vein of 1-day-old KI mice. Cardiac function was analyzed at different postnatal times until 34 wks by echocardiography and compared to age-matched wild-type (WT) mice. Levels of cMyBP-C protein were determined by Western blot and localization of transgenic protein was evaluated by immunofluorescence with specific antibodies in cardiac sections. Results: KI mice did not show a cardiac phenotype at postnatal day 1 (P1), but exhibited reduced fractional area shortening (FAS) at P2 and LVH at P3. AAV9-mediated Mybpc3 gene transfer dose-dependently and partially prevented the reduction of FAS and increase in LVM/BW ratio over time. In particular, doses of 10^12 and of 3x10^12 Vg/mouse fully prevented the development of cardiac dysfunction and hypertrophy 24 wks post-administration, respectively. The amount of FLAG-cMyBP-C and therefore of total-cMyBP-C was dose-dependently increased in ventricular tissue of AAV9-FLAG-Mybpc3-treated mice. FLAG-cMyBP-C protein was restricted to the heart and was not found in liver and skeletal muscle. In addition, immunofluorescence of cardiac sections showed the classical sarcomere striation pattern of cMyBP-C as doublet in the A-band. Conclusions: This study provides proof-of-principle of gene therapy as a feasible treatment for HCM associated with MYBPC3 mutation. This therapeutic strategy is particularly attractive for severe forms of HCM affecting children.